Islamic Fiscal Policy: A Scientometric Analysis Using R - Muhammad Raihan Gunawan; Fauzi Herman (SMART Insight, 2022)
This scientometric research looks at the current situation of various studies on Islamic fiscal policy published in journals that have digital-object identifiers (DOI). This research focuses on the features and trends of keywords, authors, and journals. We use research articles (metadata) from Dimension (https://dimension.ai). The research dataset was found using a search that was last updated on May 31, 2022. A descriptive statistical approach was used to determine the bibliometric map, and bibliometric analysis was performed using R Biblioshiny. In recent years, there has been a substantial increase in the number of studies addressing the topic of Islamic fiscal policy. Many publications publish on this topic, the most prominent of which is the United Nations Treaty Series journal, which features multiple authors exploring the topic using a variety of keywords. Chouwdhury MA, Kuran T, and Mirakhor A are the most prolific authors. The keywords most frequently used are 'Economic, waqf, and public.' This review provides an overview of research trends, keywords, journals, and authors in the most popular papers on Islamic fiscal policy, as well as providing information for academics specializing in this field.